(untitled) (Information Horizons: American Journal of Library and Information Science Innovation (2993-2777), 2024)
This article covers the organization of accounting for fixed assets, its organization in Uzbekistan in accordance with national standards, as well as their technical service and solution, organization, accounting for depreciation (amortization) of fixed assets, taking into account the conditions in this field.